Innovative Educational Technologies in Professional Training of Future Specialists in the Field Education - Ilmira Ismailovna Setsaliyeva; Abbosjon Abrorjonugli Abdullayev (Researchparks Publishing, 2022)
Comprehensive development and education of the individual in accordance with public needs is the primary task facing Uzbekistan pedagogy. The introduction of innovative methods in education is designed to improve learning outcomes. At the same time, the imperfection and inertness of the educational system complicates the development of the new, which significantly slows down the process. Nevertheless, innovative technologies in education remain an effective trump card of the state, which sets the task of raising the standard of living of citizens and leading the country out of a state of economic stagnation.